Unraveling the role of Intralipid in suppressing off-target delivery and augmenting the therapeutic effects of anticancer nanomedicines. (May 2021) - Islam, Rayhanul; Gao, Shanghui; Islam, Waliul; Šubr, Vladimír; Zhou, Jian-Rong; Yokomizo, Kazumi; Etrych, Tomáš; Maeda, Hiroshi; Fang, Jun
Abstract: Intralipid, a clinically used lipid emulsion, was reportedly utilized as one strategy to suppress off-target delivery of anticancer nanomedicines; Intralipid also effectively improved drug delivery to tumors and produced better therapeutic effects. However, the mechanisms involved—the why and how—in Intralipid's facilitation of delivery of nanomedicines to tumors have not yet been reported in detail. In this study, we investigated Intralipid and discovered the beneficial effects of Intralipid pretreatment when using three anticancer nanomedicines, including the clinically approved drug doxorubicin (Doxil). Intralipid pretreatment induced a 40% reduction in liver uptake of a polymeric nanoprobe used in photodynamic therapy as well as a 1.5-fold-increased nanomedicine accumulation in tumors. This increased accumulation consequently led to significantly better therapeutic effects, and this finding was validated by using Doxil. As an interesting result, Intralipid pretreatment significantly prolonged the plasma half-life of nanomedicines in normal healthy mice but not in tumor-bearing mice, which suggests that tumors become an alternative route of nanomedicine delivery when liver delivery is suppressed. Also, we found markedly increased tumor blood flow, as measured by fluorescence angiography, and significantly lower blood viscosity after Intralipid pretreatment. All our results together indicate that Intralipid treatment not only suppressed off-target nanomedicine delivery by the reticuloendothelial system, but more important, it enhanced nanomedicine delivery to tumors by improving tumor blood flow, which is key to satisfactory drug delivery via the enhanced permeability and retention effect. Significantly better therapeutic outcomes were thus achieved by the strategy of combining utilization of nanomedicines and Intralipid pretreatment. Statement of significance: Off-target delivery to organs such as the liver and obstructed tumor blood flow as is often seen in advanced cancers are major barriers to the therapeutic efficacy of anticancer nanomedicines. Intralipid has been shown effective for suppressing nanomedicine accumulation in the liver, resulting in improved anticancer effects. Unraveling the mechanisms involved in this process will be greatly helpful for the clinical application of anticancer nanomedicines. We reported here that Intralipid could also significantly increase tumor delivery of nanomedicine, which is beneficial for improving tumor blood flow and lowering blood viscosity. To our knowledge, this is the first study to investigate the role of Intralipid in this regard. This knowledge provides a solid rationale for the use of Intralipid in combination with anticancer nanomedicines. Graphical abstract: Image, graphical abstract